Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1038/nn.4163
|View full text |Cite
|
Sign up to set email alerts
|

Decreased amyloid-β and increased neuronal hyperactivity by immunotherapy in Alzheimer's models

Abstract: Among the most promising approaches for treating Alzheimer's disease is immunotherapy with amyloid-β (Aβ)-targeting antibodies. Using in vivo two-photon imaging in mouse models, we found that two different antibodies to Aβ used for treatment were ineffective at repairing neuronal dysfunction and caused an increase in cortical hyperactivity. This unexpected finding provides a possible cellular explanation for the lack of cognitive improvement by immunotherapy in human studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
90
3
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 126 publications
(100 citation statements)
references
References 32 publications
3
90
3
1
Order By: Relevance
“…Our results further suggest that neuronal hyperactivity within amyloid plaque-bearing local circuits is likely due to prefibrillary Aβ species, which form a halo around the plaque cores. The findings are unexpected in view of previous evidence indicating that at such advanced disease stages, many pathological and cellular processes are chronic and mostly irreversible (7,8,(23)(24)(25). In fact, we found that most dysfunctional neurons in the amyloid-plaque bearing neocortex are still viable, and that their "hyperactive phenotype" can be reversed by reducing Aβ in the brain.…”
Section: Discussioncontrasting
confidence: 90%
See 4 more Smart Citations
“…Our results further suggest that neuronal hyperactivity within amyloid plaque-bearing local circuits is likely due to prefibrillary Aβ species, which form a halo around the plaque cores. The findings are unexpected in view of previous evidence indicating that at such advanced disease stages, many pathological and cellular processes are chronic and mostly irreversible (7,8,(23)(24)(25). In fact, we found that most dysfunctional neurons in the amyloid-plaque bearing neocortex are still viable, and that their "hyperactive phenotype" can be reversed by reducing Aβ in the brain.…”
Section: Discussioncontrasting
confidence: 90%
“…Experiments were performed on female APP23xPS45 double-transgenic mice aged >6 mo overexpressing the human APP with the Swedish mutation (670/671) and the human G384A-mutated PS1 (7,10,11,17,(35)(36)(37). At this age, mice exhibit widespread cerebral Aβ pathology (10,17,36), neuropil dystrophy (10), and astrocytic (17,38) and microglia (39) impairments, as well as learning and memory deficits (10,11,17).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations